2018
DOI: 10.5194/amt-11-3883-2018
|View full text |Cite
|
Sign up to set email alerts
|

From model to radar variables: a new forward polarimetric radar operator for COSMO

Abstract: Abstract. In this work, a new forward polarimetric radar operator for the COSMO numerical weather prediction (NWP) model is proposed. This operator is able to simulate measurements of radar reflectivity at horizontal polarization, differential reflectivity as well as specific differential phase shift and Doppler variables for ground based or spaceborne radar scans from atmospheric conditions simulated by COSMO. The operator includes a new Doppler scheme, which allows estimation of the full Doppler spectrum, as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 65 publications
1
29
0
Order By: Relevance
“…Efforts to develop additional PRFOs have renewed over the past several years (Augros et al [68], Wolfensberger and Berne [69], Matsui et al [70], Mendrok et al [71], and Oue et al [72]). Augros et al [68] created a PRFO for the French nonhydrostatic mesoscale research NWP model Meso-NH (Lafore et al [73]).…”
Section: Polarimetric Radar Forward Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts to develop additional PRFOs have renewed over the past several years (Augros et al [68], Wolfensberger and Berne [69], Matsui et al [70], Mendrok et al [71], and Oue et al [72]). Augros et al [68] created a PRFO for the French nonhydrostatic mesoscale research NWP model Meso-NH (Lafore et al [73]).…”
Section: Polarimetric Radar Forward Operatorsmentioning
confidence: 99%
“…Beam broadening and bending are accounted for along with attenuation in rain. Wolfensberger and Berne [69] developed an advanced PRFO for COSMO, and Mendrok et al [71] reported on the progress to add polarimetric capabilities to the Efficient Modular Volume scanning RADar Operator (EMVORADO; Zheng et al [74]) in COSMO and the ICOsahedral Nonhydrostatic model (ICON). These PRFOs include the effects of beam broadening, with the latter two computing Doppler radar variables (including the Doppler spectrum in Wolfensberger and Berne [69]).…”
Section: Polarimetric Radar Forward Operatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These errors are of three kinds: (i) measurement errors of the radar moments (Z, Z dr , φ dp ), (ii) conversion errors in the quantitative precipitation estimation of the precipitation from the radar moments and (iii) extrapolation errors in the determination of the precipitation falling at the ground from the estimations obtained at beam heights. In recent years, significant progress has been made to reduce the first two types of errors by better controlling the quality of the polarimetric parameters (calibration of Z and Z dr , adaptive smoothing of φ dp , attenuation correction) (Bringi et al, 2001;Gourley et al, 2009;Yu et al, 2018) and by combining the polarimetric moments to estimate the precipitation with minimal uncertainty (Ryzhkov et al, 2005;Tabary et al, 2011;Figueras i Ventura et al, 2012). However, the final step of estimating the precipitation at the ground remains a major challenge in particular in mountainous regions where lower beams can be partially or totally blocked (Creutin et al, 1997;Smith, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that synthetic yet realistic radar observations can be obtained by applying a radar simulator to model outputs (Caumont et al, 2006;Jung et al, 2008;Pfeifer et al, 2008;Ryzhkov et al, 2011;Wolfensberger and Berne, 2018). The VPR estimation and correction is a major step in radar data processing that determines the quality of radar precipitation that would be observed at the ground.…”
Section: Introductionmentioning
confidence: 99%